COĞRAFİ KEŞİFLER KONUSUNUN ÖĞRETİLMESİNE İLİŞKİN ÖĞRETMEN GÖRÜŞLERİ. - Cengiz, Meryem; Demirbaş, Çağrı Öztürk (Mehmet Akif Ersoy University Journal of Education Faculty)
The discovery of unknown parts of the world formed the basis of geographical discoveries. This study, which aims to determine the views of teachers on teaching the subject of geographical discoveries in the secondary school social studies 7th grade textbooks, is a qualitative study. It was applied to 20 teachers teaching the 7th grade social studies course. A semi-structured interview form was applied to the teachers. Phenomenology, one of the qualitative research designs, was used. In the research, the necessity of the subject, the learning and teaching process, the problems encountered and the views of the social studies teachers about the teaching of the subject of geographical discoveries in the textbook were discussed. Teachers found it necessary to teach the subject, important to teach it, and thought that it contributed to the objectives of the lesson. In the learning process, the teachers used mostly questions and answers when introducing the subject, and mostly straight lectures while teaching the lesson, and they used maps the most as a material. The time given to the subject was found insufficient by the teachers. The problems experienced by the teachers on the subject are mostly student-related problems. It was concluded that the misconceptions formed by the students were eliminated mainly by explaining.